1988
DOI: 10.1210/jcem-66-1-242
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Nocturnal Melatonin Secretion in Women With Functional Hypothalamic Amenorrhea

Abstract: Plasma melatonin levels were determined by a sensitive RIA at 30 min intervals for 24h in 7 women with functional hypothalamic amenorrhea (HA) and in 7 age and season matched normal cycling women in the early follicular phase (NC). While daytime melatonin concentrations were nondetectable in both groups, the integrated nocturnal levels were 3-fold greater in HA (244 +/- 58 (SE) vs 74 +/- 32 pmol-min/Lx10(3), p less than 0.005). This melatonin increase in HA was due to an elevated peak amplitude (p less than 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
5

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(75 citation statements)
references
References 26 publications
6
64
0
5
Order By: Relevance
“…When first assessed, this patient's plasma melatonin concentrations were much higher than those reported for hypothalamic amenorrhea, and they declined gradually to the normal range over the course of several years. Interestingly, this patient achieved fertility spontaneously while the melatonin concentrations were still elevated at levels comparable to those reported for hypothalamic amenorrhea [Berga et al, 1988;Brzezinski et al, 19881. To explain fertility despite hypermelatoninemia, the authors of that case report proposed that the important feature of melatonin secretion in relation to the function of the hypothalamic-pituitary-gonadal axis is the change in amplitude or duration of the nocturnal melatonin rise, rather than the absolute values of melatonin concentrations [Puig-Doming0 et al, 19921.…”
Section: Melatonin Secretory Profile In Adultssupporting
confidence: 69%
See 1 more Smart Citation
“…When first assessed, this patient's plasma melatonin concentrations were much higher than those reported for hypothalamic amenorrhea, and they declined gradually to the normal range over the course of several years. Interestingly, this patient achieved fertility spontaneously while the melatonin concentrations were still elevated at levels comparable to those reported for hypothalamic amenorrhea [Berga et al, 1988;Brzezinski et al, 19881. To explain fertility despite hypermelatoninemia, the authors of that case report proposed that the important feature of melatonin secretion in relation to the function of the hypothalamic-pituitary-gonadal axis is the change in amplitude or duration of the nocturnal melatonin rise, rather than the absolute values of melatonin concentrations [Puig-Doming0 et al, 19921.…”
Section: Melatonin Secretory Profile In Adultssupporting
confidence: 69%
“…Applying careful methods to characterize the phases of the menstrual cycle and taking frequent blood samples to determine the melatonin secretory profile, Brzezinski et al [ 19881 and Berga and Yen [1990] have demonstrated that the plasma melatonin profile is stable during the various phases of ovarian cycles. Augmented nocturnal melatonin secretion, however, has been reported in hypothalamic amenorrhea [Berga et al, 1988;Brzezinski et al, 19881. Recently Puig-Doming0 et al…”
Section: Melatonin Secretory Profile In Adultsmentioning
confidence: 99%
“…Bu verilerle, pineal melatonin salgılanmasının yeme bozukluğu olan kadınlarda (depresyon faktörü söz konusu değilken) değişme-diği ve bu grupta amenorenin sıklıkla görülmesine melatoninin yol açmadığı vurgulanmıştır. Fonksiyonel hipotalamik amenoreli kadınlar ile normal adet gören foliküler fazın başında olan kadınların 24 saatlik serum melatonin düzeylerinin karşılaştı-rıldığı bir çalışmada hipotalamik amenoreli kadın-larda nokturnal melatonin salgısı normal kadınla-ra göre daha erken başlamış, daha geç bitmiş ve melatonin düzeyi 3 kat fazla çıkmıştır (28). Siklustaki kadınlarda günlük yüksek dozlarda melatoninin kronik uygulaması plazma LH'sını belirgin olarak baskılamış ama 4 aylık tedaviden sonra bile estradiolü inhibe edememiştir.…”
Section: T Ta Ar Ri Ih Hç çE Eunclassified
“…Melatonin is thought to be involved in the precocious puberty process (20). Melatonin levels were found to be low in precocious puberty (20,21) and high in women with stress-induced, exercise-induced, or functional hypothalamic hypogonadism (22)(23)(24). It has been postulated that, before puberty, the decline of serum melatonin represents the activating signal for the hypothalamic pulsatile secretion of gonadotropinreleasing hormone, which is necessary for the activation of the gonadotropic axis and, thereafter, the onset of pubertal changes (25).…”
Section: Introductionmentioning
confidence: 99%